Thymic-derived tolerizing dendritic cells are upregulated in the spleen upon treatment with intravenous immunoglobulin in a murine model of immune thrombocytopenia. (4th July 2017) - Kapur, Rick; Aslam, Rukhsana; Kim, Michael; Guo, Li; Ni, Heyu; Segel, George B.; Semple, John W.
Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder characterized by low platelet counts. First-line treatment includes intravenous immunoglobulin (IVIg), however, its working mechanism remains incompletely understood. We investigated splenic and thymic dendritic cell (DC) subsets upon IVIg treatment in a well-characterized active murine model of ITP. During active disease, there was a significant peripheral deficiency of splenic tolerizing SIRPα+ DCs which could be rescued by IVIg therapy, increasing platelet counts. These splenic tolerizing DC changes were associated with an abrogation of the thymic-retention of tolerizing DCs, suggesting that IVIg may raise platelet counts in ITP by modulating peripheral numbers of tolerizing DCs.